The role of temozolomide as adjuvant therapy in glioblastoma management: a systematic review and meta-analysis. - Made Agus Mahendra Inggas; Utsav Patel; Jeremiah Hilkiah Wijaya; Nina Otinashvili; Vyshnav Rajagopal Menon; Abhay Krishnan Iyer; Tawfiq Turjman; Surbhi Dadwal; Mari Gadaevi; Azada Ismayilova; Shiva Jashwanth Gaddam; Prakriti Arya; et al. (BMC Cancer)
Abstract Introduction The persistent challenge of temozolomide (TMZ) resistance and the eventual recurrence of tumors underscore the need for ongoing research and the development of novel therapeutic strategies. We aim to consolidate existing evidence related to the safety and efficacy of TMZ as adjuvant therapy to radiotherapy (RT). Methods Various electronic platforms were used to conduct a systematic literature review, including PubMed, Europe PMC, SCOPUS, and clinicaltrials.gov. The approach aimed to identify all pertinent studies published up to July 25, 2024. The search incorporated terms such as “glioblastoma,” “temozolomide,” “monotherapy,” and “adjuvant” alongside relevant Medical Subject Headings (MeSH). The key metrics were overall and progression-free survival, while secondary measures concentrated on treatment-related adverse effects, notably hematological issues like anemia, leukopenia, thrombocytopenia, and neutropenia. Results The overall effect estimates from the forest plots show significant differences favoring TMZ + RT over RT alone. The HR for overall survival is 0.64 (95% CI: 0.58, 0.71), showing a considerable improvement with TMZ + RT. Progression-free survival shows a HR of 0.51 (95% CI: 0.45, 0.58), also demonstrating a significant benefit for TMZ + RT. Conclusions Combining TMZ with RT generally leads to better overall and progression-free survival outcomes compared to RT alone. However, the two treatment groups have similar toxicity.